COVID-19-Associated Cerebral Venous Sinus Thrombosis: A Case Report and Review of the Literature - Adalet AYPAK; Esragül AKINCI; Abdulsamet ERDEN; Banu ÇAKIR TOPÇU; Orhan KÜÇÜKŞAHİN; Rahmet GÜNER (Mediterranean Journal of Infection, Microbes and Antimicrobials)
Coronavirus disease-2019 (COVID-19) is a global health problem causing morbidity and mortality. It has a clinical spectrum ranging from an absence of symptoms to acute respiratory distress syndrome. A new COVID-19-related clinical finding is published daily. We report here a patient with COVID-19 and cerebral venous sinus thrombosis and no deep vein thrombosis or any underlying predisposing factors for hypercoagulation.